2014
DOI: 10.1039/c3ta15310j
|View full text |Cite
|
Sign up to set email alerts
|

Application of ZnxCd1−xSe-sensitized TiO2 nanotube arrays as photoanodes for solar cells

Abstract: This study reports the synthesis of Zn x Cd 1Àx Se quantum dot-sensitized titania nanotube array photoelectrodes using a successive ionic layer adsorption and reaction technique and evaluates the photoelectrochemical performance as anodes. The effect of altering the number of sensitization cycles and annealing temperature on optical and photoelectrochemical properties of prepared photoanodes was studied. Surface morphology of the sensitized tubes was analyzed by scanning electron microscopy, while the phase co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 70 publications
3
21
0
Order By: Relevance
“…The presence of GO and/or Zn x Cd y S did not affect the crystal phase of TiO 2 . The peaks at 2 θ = 26.6° related to the presence of CdS, but no significant change was observed for the CdS phase upon the incorporation of Zn in Zn x Cd y S crystallites, which indicated that the low‐dopant concentration of Zn did not affect the CdS crystal structure below the detection limit …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The presence of GO and/or Zn x Cd y S did not affect the crystal phase of TiO 2 . The peaks at 2 θ = 26.6° related to the presence of CdS, but no significant change was observed for the CdS phase upon the incorporation of Zn in Zn x Cd y S crystallites, which indicated that the low‐dopant concentration of Zn did not affect the CdS crystal structure below the detection limit …”
Section: Resultsmentioning
confidence: 96%
“…The highest steady photocurrent density of Zn x Cd y S/GO/3D‐TNTAs (12 deposition cycles) reached 1 mA cm −2 , which was roughly 10 times that of the unmodified 3D‐TNTAs (Figure d). This clearly indicates that the composite electrode made by 12 deposition cycles has greatly enhanced photocurrent production due to the loading of GO and Zn x Cd y S on the nanotubes surface, but this does not necessarily mean that more cycles (over 12 cycles) will lead to better results …”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the intrinsic electronic property and elucidate the origin of PEC performance enhancement of the Bi 2 S 3 /WO 3 photoelectrode, the MotteSchottky (MS) analysis was employed with a frequency of 1 kHz in the mixed solution of water and ethanol. The flat band potential (V fb ) and charge carrier density (N) of an electrode were determined by MS relation [60,61].…”
Section: Resultsmentioning
confidence: 99%
“…IIeVI group semiconductors (e.g., CdS, CdSe, ZnSe) have been widely chosen as sensitizer layer because of their appropriate optical properties, abundance, easy manufacture [26e29]. Compared with the most studied binary IIeVI semiconductors, ternary alloy semiconductor materials (e.g., ZnCdSe [25,30,31], ZnCdTe [32], CdSSe [33,34]) distinguish themselves by many advantages, such as the tunable band gaps [35,36], synergistic effects for the light harvesting [26,37] and higher chemical stability [38,39]. In 2013, Pan et al [39] studied the CdSe x Te 1Àx alloyed quantum dots (QD) sensitized solar cell (QDSSC) based on mesoporous TiO 2 film, and found that the CdSe x Te 1Àx QDs enormously broadened the light absorption of the QDSSC into near infrared range and the solar energy conversion efficiency reached above 6%.…”
Section: Introductionmentioning
confidence: 99%